Thermal Inactivation of Poliovirus in the Presence of Selective Organic Molecules (Cholesterol, Lecithin, Collagen, and β-Carotene) - Milo, George E. (1971)
Poliovirus type 1 strain LS-a exhibited the typical thermal inactivation pattern observed previously by other investigators for poliovirus strains sensitive to the temperatures used in these experiments. However, when the virus suspension was thermally treated at 121 C for 5 sec in the presence of 2% collagen, a stabilizing effect on the virus was observed. The stabilizing effect in the presence of other food additives, such as cholesterol, lecithin, or β-carotene, was less dramatic or there was no effect at all. Pretreatment of the cells with the same additives before inoculation induced various changes in the susceptibility of the cells to infection by poliovirus. Lecithin and cholesterol treatment appeared to increase HeLa cell susceptibility to the invading virus, thereby enhancing infectivity. Ultraviolet examination of thermally inactivated virus (121 C) suspensions did not indicate any severe denaturation of the nucleic acid core. Subsequent phenol extraction of the infectious nucleic acid from the heat-inactivated virions revealed that infectious nucleic acid was still present in the denatured heat-treated (62 to 72 C) samples of virion. The immediate past history of treatment of the uninoculated cells appeared to be important, since pretreatment of the cells with cholesterol before inoculation resulted in a noticeable increase in infectivity. In addition, cholesterol-treated uninoculated cell sheets also exhibited an increase in longevity compared to the uninoculated, untreated controls.